An analysis on the factors that impacting food security in JAPAN - Ong, Kai Feng (2024)
Food has always been the foundation for the progress of human civilization and the basic purpose of human survival. Although Japan ranks prominently in the Global Food Security Index (GFSI), much of this is due to its strong economic fundamentals. However, food systems that rely solely on economic strength are vulnerable to external influences. Due to the current external situation, people have increased concerns about the possible disruption of Japan's food supply during an emergency and whether Japan can maintain strong agricultural self-sufficiency and food security. Therefore, this study will examine the relationship between different independent variables such as Japan's GDP per capita, food imports, agricultural employment, agricultural land, fertilizer consumption, and food production index (dependent variable), and evaluate the extent to which these factors affect to Japan's food production by using the vector error correction model method (VECM). According to the results from the VECM of this study, the food production index (FPI) and employment in agriculture (EIA) are cointegrated, which also means that there is a long-term relationship between the two. In addition, in the short term, per capita GDP, food imports, agricultural employment, and agricultural land will have a corresponding positive impact on the food production index (FPI), indicating their importance in affecting Japan's food production and security. This study attempts to identify areas for improvement and propose effective policy recommendations to ensure food security and a stable food production supply in Japan, thereby creating a more reliable food production system.